Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
Objective To provide a comprehensive narrative review of the role of cell culture models in drug discovery, preclinical safety evaluation, regenerative medicine, and therapeutic innovation in otorhinolaryngology and craniofacial surgery, with emphasis on their translational value in bridging laboratory research and clinical practice. Methods A narrative review was conducted using PubMed/MEDLINE, Scopus, and Web of Science databases. Studies published between 2017 and 2026 were screened using predefined keywords related to cell culture, rhinology, drug discovery, regenerative medicine, topical therapy, and head and neck oncology. Eligible studies included in vitro investigations using validated human primary cell cultures or established cell lines relevant to otorhinolaryngology. Data on experimental models, investigated compounds, biological outcomes, and potential clinical applications were extracted and synthesized narratively by major translational research domains. Results Twenty-six eligible studies were included. Primary human nasal epithelial cells were the most frequently used model (n=13), followed by fibroblast cultures (n=5), laryngeal carcinoma cell lines (n=5), and A549 respiratory epithelial cells (n=1). The reviewed studies consistently demonstrated that cell culture models enable reliable evaluation of concentration-dependent cytotoxicity, epithelial compatibility, regenerative capacity, and antitumor activity. Natural bioactive compounds were the largest category of agents investigated, while drug repurposing emerged as a major translational strategy. Recent advances, including 3-dimensional cultures, organoids, air-liquid interface systems, and organ-on-chip technologies, have substantially improved the physiological relevance and predictive value of in vitro models. Conclusion Cell culture technologies have evolved from simple laboratory screening tools into indispensable components of translational drug development in otorhinolaryngology. These models facilitate early safety assessment, optimization of therapeutic concentrations, evaluation of regenerative and anticancer agents, and reduction of unnecessary animal experimentation. The integration of advanced in vitro platforms with emerging technologies such as artificial intelligence is expected to further accelerate precision medicine and the development of safer, more effective, and personalized therapies for upper airway and craniofacial disorders.